2010
DOI: 10.1021/ic101340a
|View full text |Cite
|
Sign up to set email alerts
|

Indium Flux-Growth of Eu2AuGe3: A New Germanide with an AlB2 Superstructure

Abstract: The germanide Eu(2)AuGe(3) was obtained as large single crystals in high yield from a reaction of the elements in liquid indium. At room temperature Eu(2)AuGe(3) crystallizes with the Ca(2)AgSi(3) type, space group Fmmm, an ordered variant of the AlB(2) type: a = 857.7(4), b = 1485.5(10), c = 900.2(4) pm. The gold and germanium atoms build up slightly distorted graphite-like layers which consist of Ge(6) and Au(2)Ge(4) hexagons, leading to two different hexagonal-prismatic coordination environments for the eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 84 publications
1
35
1
Order By: Relevance
“…τ 1 crystallizes with AlB 2 type as defined by the Rietveld refinement in Figure 10 of the X-ray powder pattern of the alloy with nominal composition Sr 30 Au 16.5 Ge 53.5 . The formation of an ordered superstructure with 2:1:3 composition, as suggested by Sebastian et al, [42] was not observed during this investigation but cannot be excluded to exist at another temperature. Besides τ 1 the alloy also contains small quantities of τ 2 and (Ge) according to the location of the sample in the three-phase field.…”
Section: The System Sr-au-gecontrasting
confidence: 44%
See 2 more Smart Citations
“…τ 1 crystallizes with AlB 2 type as defined by the Rietveld refinement in Figure 10 of the X-ray powder pattern of the alloy with nominal composition Sr 30 Au 16.5 Ge 53.5 . The formation of an ordered superstructure with 2:1:3 composition, as suggested by Sebastian et al, [42] was not observed during this investigation but cannot be excluded to exist at another temperature. Besides τ 1 the alloy also contains small quantities of τ 2 and (Ge) according to the location of the sample in the three-phase field.…”
Section: The System Sr-au-gecontrasting
confidence: 44%
“…Similar to the high temperature modification, β-K 4 ᮀ 2 P 6 type (see also [40] General descriptions of the AlB 2 family including the ordered 2:1:3 superstructures are given in an review article of Hoffmann and Pöttgen [41] and further discussions on 2:1:3 superstructure formations can be found in the article of the isotypic compound Eu 2 AuGe 3 . [42] With all distances Si-(Au,Si) and (Au,Si)-(Au,Si) being smaller than 2.50 Å, we may count on strong covalent bonding within the planar Au,Si networks in Sr 2.00 Au 1.01 Si 2.82 ᮀ 0.18 . As has been pointed out earlier, [42] direct Au-Au (d 10 -d 10 ) contacts are the driving force for the formation of puckered hexagonal layers, which so far have not been found in 2:1:3 compounds.…”
Section: The System Sr-au-simentioning
confidence: 97%
See 1 more Smart Citation
“…The origins of these wide ranges of fascinating and anomalous physical properties are associated with the interplay of interactions between the localized 4f (or 5f) electrons of the rare earth atoms and the delocalized conduction electrons of the transition metal atoms. Among the RE-T-X (RE = rare earths, T = transition metals, X = p-block elements) intermetallics, compounds having general the formula RE 2 TX 3 are extensively studied for their interesting structural and physical properties [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. These compounds generally crystallize in the AlB 2 structure type and its ordered superstructures [24].…”
Section: Introductionmentioning
confidence: 99%
“…Several examples are summarized in [4]. Indium on the other hand seems to be a good candidate for a non-reactive flux, as recently shown for the synthesis of DyNiGe 2 [12], Eu 2 AuGe 3 [13] and Yb 5 Ni 4 Ge 10 [14] crystals. Good results have also been obtained with bismuth fluxes for the phosphides RERh 6 P 4 (RE = Sc, Yb, Lu) [15], and this has been applied to the germanide CeRh 6 Ge 4 [16].…”
Section: Introductionmentioning
confidence: 91%